Difficulties Encountered by English Teachers in Using Storytelling to Teach Young Learners - Melfan Widia Krisdayanti Hulu (The Study Program of English Education of Palangka Raya University, 2024)
Teachers of English utilize storytelling as a common strategy while teaching second languages, especially to young learners. However, because young learners have various features when it comes to second language proficiency, English teachers will find it challenging to use storytelling in these courses. The purpose of this study was to identify the difficulties faced by English teachers while teaching through these methods. The qualitative research technique was utilized in conjunction with the phenomenological design. The three English teachers were selected as participants, who were teaching to five grade students through the purposive sampling technique. Self-developed semi-structured interviews were carried out, and the data were transcribed into codes and themes. This study found that teachers found it difficult to find stories that were suitable for children, did not know the criteria for stories that were suitable for children, lacked the confidence to compose children's own stories, and had very limited time available (75 minutes once a week). It is recommended that resource rooms be established to provide English teachers with the greatest possible training opportunities.